Effects of Prescribed Fire Timing on Stocker Cattle Performance and Native Plant Composition: Year 3 of 6 - Z. M. Duncan; A. J. Tajchman; M. P. Ramirez; J. Lemmon; K. J. Suhr; W. R. Hollenbeck; D. A. Blasi; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective of this experiment was to document the effects of prescribed-fire timing on stocker cattle performance, soil cover, and plant species composition over a six-year period. Study Description:Yearling stocker cattle were assigned to one of three prescribed-burn treatments: spring (April 9 ± 5.1 days), summer (August 23 ± 4.9 days), or fall (September 29 ± 8.7 days). Calves were grazed from May to August for 90 days. Individual body weights (BW) were recorded at the beginning and end of the grazing season to determine total BW gains and average daily gains. Native plant composition and soil cover were evaluated annually using a modified step-point method. The Bottom Line:We interpreted these data to suggest that summer-season prescribed fire could be used to manage sericea lespedeza (Lespedeza cuneata) infestations without reducing grazing performance of yearling cattle or damaging the vigor of native warm-season plant populations.
Keywords: grazing; prescribed fire; sericea lespedeza